Use of infographics among selected libraries in Quezon City an exploratory study - Samson, Patricia B. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
Aside from its purpose to inform the users about the different services and collections of the library, a library instruction also supports the life-long learning of its users. Library instruction programs are thus expected to adapt to newer and more effective instruction methods. The study focused on the librarians' preferences in using and creating infographics, a form of data visualization, in library instruction. The study sought to assess the instructional materials used for library instruction; the types of infographics used in library instructions; the preferences of participants in creating and using infographics.